Impact of a pilot NHS-funded sore throat test and treat service in community pharmacies on provision and quality of patient care. Issue 1 (28th February 2020) - Mantzourani, Efi; Evans, Andrew; Cannings-John, Rebecca; Ahmed, Haroon; Hood, Kerenza; Reid, Nicholas; Howe, Robin; Williams, Emma; Way, Cheryl
Abstract : Objective: A National Health Service (NHS)-funded sore throat test and treat (STTT) service was introduced in selected pharmacies in two local health boards in Wales, as an extension to the national pharmacy common ailment scheme. The aim of this study was to evaluate the impact of STTT on provision and quality of patient care, namely antibiotic use, patient safety and general practitioner (GP) consultation rates. Methods: Secondary analyses of STTT consultation data to describe service outcomes, and routine data to explore changes in antibiotic prescribing and the prevalence of complications. Data were also collected from one GP practice to explore the feasibility of measuring changes in sore throat consultation rates in general practice. Results: Less than 20% of 1725 consultations resulted in antibiotic supply. The availability of STTT was associated with greater reductions in prescriptions for phenoxymethylpenicillin than in areas where STTT was not available (−3.8% and −3.4%, difference 0.4%). When pharmacy supplies were included, the reductions in the supply of the antibiotic were similar. No increase in the monthly number of incidents of quinsy was detected, and patients were appropriately referred to other healthcare professionals during pharmacy consultations. GP consultation rates since introduction of STTT were found to be lower than the equivalent monthly average since 2014. Conclusions: Data from the first 5 months of the STTT service suggest that it may have a role in safely rebalancing uncomplicated sore throat management from general practice to community pharmacies while continuing to promote antibiotic stewardship.